Aquaporin-4-positive neuromyelitis optica in a male Caucasian patient: A rare demographic presentation - Monideep Ghosh; Nesta Baxter; Michael Homer-Ward (SAGE Open Medical Case Reports)
Neuromyelitis optica with a positive aquaporin-4 antibody is a rare autoimmune condition, which has a higher prevalence in females, and disproportionately affects Black and Asian persons with a typical age of first presentation between the ages of 30 and 40. We report a unique case of a 69-year-old Caucasian male who presented following a fall along with generalised weakness, unilateral myotomal pain, and urinary dysfunction. His medical history included two previous venous thromboembolic events, for which he was anticoagulated with warfarin. Extensive investigations, including MRI of the whole spine and lumbar puncture, revealed longitudinally extensive transverse myelitis and a positive aquaporin-4 antibody, confirming neuromyelitis optica. The patient was treated with intravenous methylprednisolone, plasma exchange, and immunoglobulin therapy, followed by rehabilitation. This case highlights the importance of considering neuromyelitis optica in atypical patient demographics and that early recognition through neurological assessment, imaging, and antibody testing is critical in preventing severe disability.